The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1080/01431161.2013.788262
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil moisture and wind speed on aerosol optical thickness retrieval in a desert environment using SEVIRI thermal channels

Abstract: Dust emission and deposition are associated with several factors such as surface roughness, land cover, soil properties, soil moisture (SM), and wind speed (WS). A combination of land surface and remote-sensing models has recently been investigated for dust detection and monitoring. The thermal bands of the Meteosat Second Generation Spinning Enhanced Visible and Infrared Imager (MSG/SEVIRI) satellite are widely used for qualitative detection of dust over desert because of their high spectral and temporal reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Satellite observations, however, have some limitations that result in false identification of dust sources in some areas. One such area is where persistent dust transport/deposition takes place, and another is where pollution/biomass burning contributes significantly to the total dust load [e.g., Schepanski et al ., ; Parajuli et al ., ]. Some efforts have been made recently to improve dust source characterization by eliminating these false dust source areas.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite observations, however, have some limitations that result in false identification of dust sources in some areas. One such area is where persistent dust transport/deposition takes place, and another is where pollution/biomass burning contributes significantly to the total dust load [e.g., Schepanski et al ., ; Parajuli et al ., ]. Some efforts have been made recently to improve dust source characterization by eliminating these false dust source areas.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques of detection and aerosol property remote sensing have been successfully applied to SEVIRI measurements (Brindley and Russell, 2006;Brindley et al, 2012;De Pape and Dewitte, 2008;Li et al, 2007;Parajuli et al, 2013;Romano et al, 2013;Sannazzaro et al, 2014). These algorithms have been validated and inter-compared (Banks and Brindley, 2013;Breon et al, 2011;Schepanski et al, 2012).…”
Section: The Crew Databasementioning
confidence: 99%
“…However, at Liwa the dust emission is weak, though the wind speeds are higher, and these could be due to the peculiarities of the soil and surface properties. This result confirms the previously obtained result, which found that the UAE is not a strong source of dust [ Eck et al ., ; Parajuli et al ., ]. Rather, the aerosol loading over the UAE region is greatly influenced by the long‐range transported dust.…”
Section: Resultsmentioning
confidence: 99%
“…This large variability could be attributed to the high frequency of occurrence, as well as the intensity of dust events. In fact, recent studies show that UAE is not a strong source of dust, and the aerosol properties at those locations are strongly modulated by the long‐range dust transport [ Eck et al ., ; Parajuli et al ., ; Gherboudj and Ghedira , ].…”
Section: Description Of the Input Datamentioning
confidence: 99%